2013
DOI: 10.1074/jbc.m112.393108
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-degrading Enzyme (IDE)

Abstract: Background: Insulin-degrading enzyme (IDE) is a highly conserved metallopeptidase initially described because of its ability to degrade insulin. Results: (i) IDE expression is stress-inducible; (ii) IDE concentration is up-regulated in some CNS tumors; (iii) IDE downregulation impairs SHSY5Y cell proliferation/viability. Conclusion: IDE is a multifunctional protein.Significance: IDE is a novel HSP with important implications in cell growth regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 42 publications
5
37
0
Order By: Relevance
“…IDE is expressed in all tissues and its levels can be modulated by many signals, including cellular stress, glucagon, and free fatty acids [4, 8, 9]. It is localized in the cytosol and growing evidence indicates that its proteolytic activity is subjected to complicated regulation inside cells.…”
Section: Cellular Regulation Of Idementioning
confidence: 99%
“…IDE is expressed in all tissues and its levels can be modulated by many signals, including cellular stress, glucagon, and free fatty acids [4, 8, 9]. It is localized in the cytosol and growing evidence indicates that its proteolytic activity is subjected to complicated regulation inside cells.…”
Section: Cellular Regulation Of Idementioning
confidence: 99%
“…lysosomes), as reported in the liver [13, 14]. Protein disulfide isomerase and cathepsin D are involved in insulin metabolism but IDE is the major enzyme responsible for degrading insulin [15, 16]; Ide null mice display hyperinsulinaemia and glucose intolerance [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Treatment of hippocampal neurons with the phosphoinositide 3-kinase inhibitors wortmannin and LY 294002 blunts the upregulation of IDE caused by insulin [18]. By contrast, all trans -retinoic acid decreases IDE expression and activity in several neuroblastoma cell lines [16]. However, the renal mechanisms involved in the regulation of IDE expression are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the transgenic overexpression of IDE results in lowered Aβ levels and reduced or completely prevented the plaque formation observed in AD [ 21 ]. More recently, it has been reported that IDE, apart from regulating insulin [ 22 ] and Aβ peptides levels [ 23 ], is overexpressed in vivo in tumors of the CNS, and a novel role for IDE as a heat shock protein has also been proposed [ 24 ].…”
Section: Introductionmentioning
confidence: 99%